2018
DOI: 10.1111/bjd.16137
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis is associated with cutaneous inflammation in the imiquimod-induced murine model of psoriasiform dermatitis

Abstract: These results indicate that liver inflammation and fibrosis are associated with experimental psoriasiform dermatitis. Our results suggest that psoriatic inflammation may be associated with specific liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In response to profibrotic stimulus, the quiescent HSCs will transform into activated fibrogenic myofibroblasts with a characteristic increase of Collagen‐1 and α‐SMA and release of lipid droplets (Hernandez‐Gea & Friedman, 2012; Kisseleva, 2017). It is well known that inflammation and oxidative stress serve as an inducer to liver fibrosis and HSCs activation (Fabregat et al, 2016; Vasseur et al, 2018). Moreover, our previous study has demonstrated the crucial role of the inflammatory response in HSCs activation during NaAsO 2 exposure (Tao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In response to profibrotic stimulus, the quiescent HSCs will transform into activated fibrogenic myofibroblasts with a characteristic increase of Collagen‐1 and α‐SMA and release of lipid droplets (Hernandez‐Gea & Friedman, 2012; Kisseleva, 2017). It is well known that inflammation and oxidative stress serve as an inducer to liver fibrosis and HSCs activation (Fabregat et al, 2016; Vasseur et al, 2018). Moreover, our previous study has demonstrated the crucial role of the inflammatory response in HSCs activation during NaAsO 2 exposure (Tao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This study provides additional evidence that psoriasis contributes to the development of liver fibrosis . Effective management of psoriasis may go beyond improving skin disease and contribute to better long‐term, liver‐related patient outcomes.…”
mentioning
confidence: 78%
“…All mice were assessed with an adapted PASI score, liver function tests and liver histopathology (the primary outcome). The Aldara‐treated mice had a significantly higher mean aspartate aminotransferase ( P = 0·001) and a significantly greater surface area of hepatic collagen deposition (indicating liver fibrosis) compared with the control group ( P = 0·02) …”
mentioning
confidence: 99%
See 2 more Smart Citations